Extensive tumoral melanosis associated with ipilimumab‐treated melanoma. (1st August 2016) - Staser, K.; Chen, D.; Solus, J.; Rosman, I.S.; Schaffer, A.; Cornelius, L.; Linette, G.P.; Fields, R.C.
Summary: Tumoral melanosis describes a pigmented lesion clinically similar to melanoma but on histology reveals dense aggregates of melanin‐laden, benign macrophages without malignant cells. In the few reported cases so far, tumoral melanosis has arisen in the skin or lymph node of a patient with a regressed melanoma or an epithelioid tumour. As a marker of regressed primary melanoma, its discovery may prompt investigation and surveillance for undiagnosed local or metastatic disease. Here, we present a unique case of extensive tumoral melanosis arising during ipilimumab treatment of in‐transit metastases from a previously excised melanoma.